Myeloid PFKFB3-mediated glycolysis promotes kidney fibrosis - Yang, Qiuhua; Huo, Emily; Cai, Yongfeng; Zhang, Zhidan; Dong, Charles; Asara, John M.; Shi, Huidong; Wei, Qingqing (Frontiers in Immunology, 2023)
Excessive renal fibrosis is a common pathology in progressive chronic kidney diseases. Inflammatory injury and aberrant repair processes contribute to the development of kidney fibrosis. Myeloid cells, particularly monocytes/macrophages, play a crucial role in kidney fibrosis by releasing their proinflammatory cytokines and extracellular matrix components such as collagen and fibronectin into the microenvironment of the injured kidney. Numerous signaling pathways have been identified in relation to these activities. However, the involvement of metabolic pathways in myeloid cell functions during the development of renal fibrosis remains understudied. In our study, we initially reanalyzed single-cell RNA sequencing data of renal myeloid cells from Dr. Denby's group and observed an increased gene expression in glycolytic pathway in myeloid cells that are critical for renal inflammation and fibrosis. To investigate the role of myeloid glycolysis in renal fibrosis, we utilized a model of unilateral ureteral obstruction in mice deficient of Pfkfb3, an activator of glycolysis, in myeloid cells (Pfkfb3 ΔMϕ ) and their wild type littermates (Pfkfb3 WT ). We observed a significant reduction in fibrosis in the obstructive kidneys of Pfkfb3 ΔMϕ mice compared to Pfkfb3 WT mice. This was accompanied by a substantial decrease in macrophage infiltration, as well as a decrease of M1 and M2 macrophages and a suppression of macrophage to obtain myofibroblast phenotype in the obstructive kidneys of Pfkfb3 ΔMϕ mice. Mechanistic studies indicate that glycolytic metabolites stabilize HIF1α, leading to alterations in macrophage phenotype that contribute to renal fibrosis. In conclusion, our study implicates that targeting myeloid glycolysis represents a novel approach to inhibit renal fibrosis.